Barrage Bartoszowice-Opatowice influence on groundwater state in adjacent areasm in 1997 = Oddziaływanie stopnia wodnego Bartoszowice - Opatowice na stany wód podziemnych terenów przyległych w 1997 roku - Małyszko, Justyna; Kubicz, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main idea of this study was to analyze an influence of altering water level, by the barrage Bartoszowice ? Opatowice, on the groundwater in adjacent areas. In this paper a physiographic characteristic of the Big Island and characteristics of barrages are presented.
Keywords: wody podziemne; wody gruntowe; stopnie piętrzące; przyrosty stanów wód; Wielka Wyspa; Odra; ground water; earth water; barrages; computer modelling; water level increase; Big Island